Exploring The Rice Supply Chain in Semarang City : An Educational Game Concept - Inaya Sari Melati; Nana Kariada Tri Martuti; Wahid Akhsin Budi Nur Shidiq (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study introduces an educational game designed to enhance students' understanding of the rice supply chain in Semarang City. The primary research objective is to provide an interactive learning tool that immerses players in the complexities of the supply chain, from rice cultivation to consumer delivery, while highlighting the roles of various stakeholders and the impact of government interventions. The study employs a qualitative approach, using interactive model to integrate case study analysis and educational game development. Data collection involves semi-structured interviews with key stakeholders and field visits, while thematic and comparative analyses are used to evaluate supply chain dynamics. By incorporating real-world examples of supply chain optimization, the game provides students with hands-on experience in analyzing market dynamics, resource allocation, and technological advancements in agribusiness. This approach not only deepens engagement with complex economic structures but also prepares students for careers in logistics, policy-making, and sustainable enterprise development.